Programming of employments physical exercises for the improvement of bodily condition of children of midchildhood. - Sljusarchuk V.V; Iedynak G.A (Kharkov National Pedagogical University, 2011)
Approaches are considered on forming and realization of maintenance of physical education of students of initial school. The algorithm of programming of maintenance of lessons of physical culture is developed. The program foresees implementation of requirements of general and methodical principles of physical education, positions of theory of adaptation, requirements of the operating program. It is marked that employments must provide for: differentiated going near students, account of interests and to the wishes, motivation to independent employments by physical exercises, to providing of motor high-density. It is recommended to take into account the features of dynamics of indexes of bodily condition of children of different somatotype.